Mathematical modeling of dust-laden stream cleaning processes in radioelectronics - Batluk, Viktoriya; Romantsow, Edward; Vobliy, Oleksandr (Видавництво Львівської політехніки, 2010)
In the article mathematical model of dustladen stream cleaning processes in centrifugal- inertia apparatus and results are designs confirmed at conducted complex processes of dust collection in radioelectronics. The article describes new trends in the development of dust catching apparatuses based on the centrifugal-inertial forces, permitting to improve significantly the effectiveness of dust catching.
Keywords: dust catchers; centrifugal-inertia apparatus; mathematical model